Pour une approche sociale, écologique et économique des transitions territoriales : expériences transdisciplinaires au sein d’un Living lab - Marielle Berriet-Solliec; Dany Lapostolle; Gaëtan Mangin; Alex Roy (Développement Durable et Territoires)
When the ecological emergency calls for a deep renewal of the foundations and practices of research, the « Living lab territorial sur les transitions sociales et écologiques » of the University of Bourgogne-Franche-Comté proposes a transdisciplinary approach applied to the three research fields. The analytical grid adopted to carry out this approach combines the contributions of a critical institutionalist reading of Ostrom’s work with those of environmental justice. It makes it possible to define action-situations from which organised groups can envisage a bifurcation in territorial development trajectories and the transdisciplinarial levers that contribute to the definition of these situations. These experiments make it possible to discuss the contributions and pitfalls of transdisciplinarity and to define programmatic elements for further work.